(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Gibran KhalilGibran, one of the earliest figures of Mahjar literature, is a notable Arabintellectual of Lebanese origin who influenced both Eastern and Westernthinkers and luminaries thanks to mystic and philosophical thoughtscrystallised in his literary works. Hereby study explores the roots of hisphilosophical and mystic ideas, duly reflected in his emotional literary works,in East and West. The present paper intends to study Gibran Khalil Gibran’sliterary style in writing prose. Style in literature is the literary elementthat describes the ways that the author uses words –the author’s word choice,sentence structure, figurative language and sentence arrangement all worktogether to establish mood, images, and meaning in the text. Style describeshow the author describes events, objects, and ideas. But, in addition to thepersonal attitude, sometimes the writer’s style is not as personal as thedefinition of style suggests. It means that in many cases the style of anauthor is influenced by the general and contemporary attitudes of the era.